Exploratomy thoracotomy and rib osteosynthesis in a canine: Case report - Ohashi, Gabriel Satoru; Lima, Wagner Costa; Leal, Marcilene dos Santos; Henrique, Fernanda Vieira; Milech, Vanessa; Cunha, Ilka Catarina de Santiago; Lima, Dayanne Anunciação Silva Dantas; Filho, Manoel Lopes da Silva (Seven Editora, 2024)
A thoracotomy is a surgical incision in the chest wall to access the thoracic cavity to correct various alterations, including fractures. In cases of rib fracture correction, osteosynthesis is usually performed. The aim of this study was to report the case of a thoracotomy followed by rib osteosynthesis in a canine. A one-year-old Shih-tzu female weighing 4 kg presented with respiratory difficulties and intense pain on chest palpation and movement, inappetence and a small circular lesion in the chest area, as well as depression of the affected area. The presumptive diagnosis was made by identifying the clinical signs, which were confirmed by exploratory thoracotomy. Pre-anesthetic medication was given with tramadol, anesthetic induction with propofol, followed by total intravenous anesthesia with propofol using a syringe infusion pump. Skin diuresis was performed at the level of the 4th intercostal space, identifying muscle tears and rib fractures. For fracture repair, the hemi-clamping technique using steel wire was recommended, as well as reduction of the intercostal muscles and myorrhaphy of the thoracic muscles, using a simple continuous suture pattern with size 2-0 polyglactin 910 thread. Reduction of dead space, in the subcutaneous region, in the Cushing pattern, with size 2-0 polyglactin 910 thread and dermorraphy in the Sultan pattern with 2-0 polypropylene thread. It can be concluded that steel wire osteosynthesis was effective in resolving the animal's thoracic trauma. DOI:https://doi.org/10.56238/sevened2024.014-022